2009
DOI: 10.1016/j.neuint.2008.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying cochlear degeneration in the tubby mouse and the therapeutic effect of sulforaphane

Abstract: As with Usher syndrome observed in humans, the two main phenotypes of the tubby mouse are progressive hearing loss and retinal degeneration. Yet, the mechanism underlying the tub-related cochlear degeneration is still unclear. The reduction/oxidation (redox) imbalance in the cell is related to many kinds of diseases. This study examined expressions of thioredoxin (Trx) and Trx reductase (TrxR), an important redox system in the cell, and the related upstream and downstream proteins of the Trx/TrxR in the tubby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Interestingly, Prdx2, the only peroxiredoxin isoform tested in the Hu et al (2009) study, was 1 of the 3 most highly expressed genes in young Sprague-Dawley rat cochlea. In addition, Kong et al (2009) reported decreases in thioredoxin and thioredoxin reductase gene expression and protein levels in tubby mice ( tub/tub ) compared with heterozygous ( tub/wt ) or wild type (wt/wt). The tubby phenotype expresses late-onset weight gain and progressive loss of hair cells and retinal degeneration (Ohlemiller et al, 1995, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Prdx2, the only peroxiredoxin isoform tested in the Hu et al (2009) study, was 1 of the 3 most highly expressed genes in young Sprague-Dawley rat cochlea. In addition, Kong et al (2009) reported decreases in thioredoxin and thioredoxin reductase gene expression and protein levels in tubby mice ( tub/tub ) compared with heterozygous ( tub/wt ) or wild type (wt/wt). The tubby phenotype expresses late-onset weight gain and progressive loss of hair cells and retinal degeneration (Ohlemiller et al, 1995, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al (2009) demonstrated that sulforaphane, a naturally occurring isothiocyanate, protected against tub -related cochlear degeneration thought to be caused by downregulation of the thioredoxin antioxidant system. Thioredoxin has not been extensively studied as a treatment for acquired hearing loss (noise-induced, drug-induced, and age-related hearing loss).…”
Section: Discussionmentioning
confidence: 99%
“…Sulphoraphane [1-isothiocyanato-4-(methylsulfinyl)butane], a naturally occurring isothiocyanate derived from cruciferous vegetables is a highly potent inducer of phase 2 cytoprotective enzymes and can protect against electrophiles including carcinogens, oxidative damage and inflammation (Juge et al, 2007). A broad series of cellular, animal and human studies have demonstrated the protective potential of SFN against cancer, retinal disease, skin damage, UV irradiation (Cornblatt et al, 2007;Dinkova-Kostova et al, 2007;Talalay et al, 2007;Kong et al, 2009). However, protective effect of SFN against the toxicity of NPs is not fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The plant product sulforaphane [1-isothiocyanato-4-(methylsulfinyl)butane], derived from glucosinolates present in broccoli and other cruciferous vegetables (3), has served as a prototype for our understanding of chemoprotection by induction of phase 2 cytoprotective enzymes including NAD(P)H:quinone oxidoreductase (NQO1) (4). A broad series of animal and human studies has demonstrated the potential of sulforaphane to protect against the onset, or reduce the severity, of cancer (5)(6)(7)(8), retinal disease (9), and skin damage (10)(11)(12) resulting from oxidative or electrophile damage (5,6,8), UV irradiation (10,11), or genetic predisposition (9,13).…”
mentioning
confidence: 99%